(untitled) (Acta Scientiarum. Health Sciences, 2012)
This paper is a result of a descriptive research with a qualitative approach, aiming to examine the perception and experience of women participating in elderly groups about sexuality in the oldness. The study was conducted with 29 old women members of five different elderly groups located in the northern region of the state of Rio Grande do Sul. The data were collected through interviews with semi-structured open questions. The survey resulted in two analytical categories. The first one is associated with the participants’ understanding about sexuality in the oldness. The second one is related to new relationships as consequence of group insertion. The results indicate the importance of the awareness and the recognition of the main aspects that affect positively and negatively the practice of sexuality in the oldness, allowing the development of strategies for health education targeted to this population, considering the physical, emotional and cultural aspects of the group.